An experimental investigation on the effect of the ballasting on the coupled dynamics of the tunnel immersion system. (15th October 2019) - Song, Yue; Sun, Zhenxiang; Huang, Guoxing; Chen, Nianzhong; Gao, Xifeng
Abstract: A 3D experimental investigation on the effect of the ballasting on the coupled dynamics of the tunnel immersion system is presented in the paper. The tunnel immersion system consists of a tunnel element and two pontoons connected by suspension lines and moored with mooring lines. Tunnel/pontoon motions and suspension/mooring tensions subjected to beam irregular waves are measured synchronously. The effect of the ballasting on the coupled responses of the system is examined quantitively considering various peak wave periods and significant wave heights. Particular attention is also paid to the effect of the wave runup on the system dynamics. It is found that the ballasting would contribute to suppress the effect of the wave runup and to attenuate the roll resonance effect and thus to diminish the relative motions between the tunnel and pontoons and to reduce the occurrence probabilities of the slack and snap loadings on the suspension lines. To avoid certain risk from the wave runup effect and the roll resonance effect, it is recommended that the suspension lines not be released until the tunnel is ballasting during the practical operation. Highlights: A 3D experimental investigation on the effect of the ballasting on the coupled dynamics of the tunnel immersion system is conducted. The effect of the ballasting on the system dynamics is examined quantitively considering various wave periods and wave heights. The effect of the wave runup on the system dynamics is also investigated.